Cultivar Contributes to the Beneficial Effects of Bacillus subtilis PTA-271 and Trichoderma atroviride SC1 to Protect Grapevine Against Neofusicoccum parvum - Leal, Catarina; Richet, Nicolas; Guise, Jean-François; Gramaje, David; Armengol, Josep; Fontaine, Florence; Trotel-Aziz, Patricia (Frontiers in Microbiology, 2021)
Grapevine trunk diseases are a big threat for global viticulture. Without effective chemicals, biocontrol strategies are developed as alternatives to better cope with environmental concerns. Combination of biocontrol agents (BCA) could even improve sustainable disease management through complementary ways of protection. In this study, we evaluated the combination of Bacillus subtilis (Bs) PTA-271 and Trichoderma atroviride (Ta) SC1 for the protection of Chardonnay and Tempranillo rootlings against Neofusicoccum parvum Bt67, an aggressive pathogen associated to Botryosphaeria dieback. Indirect benefits offered by each BCA and their combination were then characterized in planta, as well as their direct benefits in vitro. Results provide evidence that (1) the cultivar contributes to the beneficial effects of Bs PTA-271 and Ta SC1 against N. parvum, and that (2) the in vitro BCA mutual antagonism switches to a strongest fungistatic effect towards Np-Bt67 in three-way confrontation test. We also report for the first time the beneficial potential of a combination of BCA against Np-Bt67 especially in Tempranillo. Our findings highlight a common feature for both cultivars: salicylic acid (SA)-dependent defenses were strongly decreased in plants protected by the BCA, in contrast with symptomatic ones. We thus suggest that (1) the high basal expression of SA-dependent defenses in Tempranillo explains its highest susceptibility to N. parvum, and that (2) the cultivar-specific responses to the beneficials Bs PTA-271 and Ta SC1 still remain to be further investigated.